Retail competitiveness in a middle sized border town (Komárno, Slovakia) - T. Sikos, Tamás; Kovács, András (Hungarian Geographical Bulletin, 2011)
Our study deals with the rapid transformation of the Slovak retail network as well as it analyzes the changes in shopping habits in Komárno, a medium sized border town in Slovakia. The first part of this paper, which is based on a desk research, analyzes the transformation of Slovak retail trade in the past few years. After providing an overlook of the national trends, the characteristic features of retail trade in Komárno are introduced. Those economic processes are pointed out which have initiated fundamental changes in the retail trade of this gateway town in southern Slovakia. In the second part of the paper we introduce the results of the fi eld research carried out on two sets of samples with 300 respondents each. The investigation was aimed at finding out about peculiarities arising from the economic recession and from the fact that Komárno lies on the border.The research was carried out between 2008 and 2010 in order to explore the effects of the downturn on shopping habits. In our research we aim to fi nd out, whether the closeness of the frontier and its distorting influence on economic processes can have a significant effect on market actors. Therefore we consider the permanent monitoring of cross-border market processes to be extremely important, so that (retail) businesses are able to react to individual rapid changes in the economic environment. Since nearly one third of the 174 micro-regions in Hungary and several regional centers are situated directly in frontier regions, it is especially important for retail businesses run in those regions to find out about the economic conditions prevailing on the other side of the border.